Numerical Simulation of the Effect of NACA 0012 Nozzle Geometry on Ducted Propeller Performance: Simulasi Numerik Pengaruh Geometri Nozzle NACA 0012 pada Performa Ducted Propeller - Suryolaksono, Muhammad Ramadhani; Bramantya, Muhammad Agung (Procedia of Engineering and Life Science, 2023)
Ducted propeller is a method on the propeller modification which added duct/nozzle on the propeller. Ducted propeller application is aimed to increase propeller thrust, increase propeller efficiency, and decrease propeller noise and vibration. In this research, a numerical simulation was conducted using ANSYS Fluent 2020 R2 with k-epsilon solver model. The aim of this research is to analyze the effect of the duct geometry using Ld/D (duct length/duct diameter) ratio. The simulation was done on two Ld/D variations at three different propeller angular velocity (1.000, 3.000, 5.000 rpm). The result of this research shows that duct with 0,6 Ld/D ratio has higher thrust force than duct with 0,5 Ld/D ratio. Meanwhile, the increase of propeller angular velocity increase propeller thrust force and fluid velocity.